A hedonic analysis of retail Italian vinegars - Luigi Galletto; Luca Rossetto (Wine Economics and Policy, 2015)
Vinegar's contribution to the Italian wine industry is significant, and Italy is the world's largest exporter of wine vinegar. Nevertheless, the features of the vinegar market have received little scholarly attention, and hedonic price analysis has not yet been applied to vinegar. Thus, through a sample survey of supermarkets, this study makes an initial attempt to investigate the most important features influencing the price of vinegar. The study reports results of a hedonic price analysis conducted on a vinegar survey that collected information about intrinsic and extrinsic cues, brand, point of sale and merchandising. Although they influence the vinegar price, bottle size and packaging features appear to mask the effects of other attributes. Modena Balsamic vinegar is a geographical denomination and commands a premium price compared with other vinegars, and vinegar prices decrease as the acidity of the content increases. Brands, bottle features and shelf display significantly affect vinegar price. Knowledge about factors affecting the vinegar price can help producers make decisions about what vinegars should be produced and how to price them, which will benefit a consistent proportion of wine and grape producers.
Keywords: 330; Hedonic price; Merchandising; Vinegar